Portal Hypertensive Gastropathy: the Twilight Zone - Rino Alvani Gani (The Indonesian Society for Digestive Endoscopy, 2014)
As one of the major complication of liver cirrhosis, portal hypertensive gastropathy (PHG) should be an interesting topic to study. Until now the exact mechanism on how this phenomenon happened is yet, not clear.1 The occurrence of PHG is quite high in patient liver cirrhosis and some relationship occurred between PHG and portal hypertension. In liver cirrhosis patients, PHG may be closely associated with hepatic vein pressure gradient(HVPG).2 However, PHG may not be directly associated with portal pressure because the mucosal damage not linearly correlated with portal hypertension, hence other mechanism involved in the etiopathogenesis of PHG. In this regards, the most important factor related to PHG is the pressure in the splanchnic vasculature. Based on histopathology study in PHG, vascular congestion resulted from increased portal pressure reduced oxygen for gastric mucosa, hence exposed mucosal layer to irritants.2 Moreover, the congestion somehow increased the production of nitric oxide, either through the shearstress locally or as the result of increase production of splanchnic vasculature due to portal hypertension.